Oxidative Coupling Reactions of Grignard Reagents with Nitrous Oxide1. Issue 24 (13th May 2013) - Kiefer, Gregor; Jeanbourquin, Loïc; Severin, Kay
<x xml:space="preserve">Abstract</x> Catalysis with laughing gas: N2O in combination with transition‐metal catalysts allow the oxidative homo‐ and cross‐coupling of Grignard reagents. The reactions can be performed under mild conditions despite the inert character of N2O.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>